Molecular Polymer Brushes Made via Ring‐Opening Metathesis Polymerization from Cleavable RAFT Macromonomers. Issue 13 (26th April 2021) - Gegenhuber, Thomas; Müllner, Markus
Abstract: The use of labile covalent bonds such as oximes and acetals for their application in the synthesis, and controlled triggered deconstruction, of molecular polymer brushes (MPBs) is reported. Macromonomers (MMs) are produced via reversible addition‐fragmentation chain transfer (RAFT) polymerization using chain transfer agents (CTAs) featuring customized labile moieties. Ring‐opening metathesis polymerization (ROMP) of the MMs using the grafting‐through approach produced MPBs in which the cleavable CTA is incorporated along the backbone, between the brush mainchain and its side chains. Degradation (i.e., the detachment of side chains) of the brush is possible through exposure to an acid stimulus. Especially, ketoxime, solketal, and ethoxyethyl (EE) acetal‐based motifs demonstrate excellent orthogonality to the polymerization protocols. This study highlights how polymer architectures can be built from, and reverted to, single polymer chains by using well‐designed CTAs in a straight‐forward approach. Abstract : Molecular polymer brushes carrying degradable moieties allow for cleaving side chains via acidic stimulus. Acid‐responsive chain transfer agents can be used to produce labile macromonomers for a grafting‐through approach to generate such acid‐degradable brushes via ring‐opening metathesis polymerization. ​